AN ANALYTICAL STUDY OF NUTRITIONAL STYLE, NUTRITIONAL STATUS, AND MENTAL HEALTH IN THE PRECONCEPTION PERIOD : (TOWARDS OPTIMAL PREGNANCY OUTCOMES) - Nur Cholila; Nur Maziyah Hurin'in; Tri Yunita Fitria Damayanti (Indonesian Midwifery and Health Sciences Journal, 2024)
Background: The preconception period is a crucial period to optimize maternal and fetal health. Preconception nutrition can affect nutritional status and mental health which has an impact on pregnancy readiness. This study aims to analyze the correlation between nutrition and nutritional status and mental health during the preconception period. Method: This study used a prospective cohort study involving women of childbearing age selected by stratified random sampling to obtain 129 respondents. Nutritional Style data were collected through FFQ questionnaires, nutritional status was measured through anthropometry and Hemoglobin examination, and mental health was measured using the DASS questionnaire. Data collection was carried out three times and analyzed using the Pearson correlation test, multiple linear regression and the Wilcoxon test for longitudinal analysis. Result: The results showed that there was no significant correlation between Nutritional Style and BMI (p-value>0.05). However, there was a significant correlation between Nutritional Style and the incidence of anemia, the strongest correlation in the first measurement (p-value 0.001) and the second measurement (p-value 0.049). A significant correlation was found between Nutritional Style and mental health, especially anxiety in the first measurement (p-value 0.022), the second measurement (p-value 0.006) and the third measurement (p-value 0.029), but not with stress and depression. There was a significant increase in nutritional status from the first to the second measurement (p-value 0.020) and the first to the third measurement (p-value 0.003). There was a significant decrease in anxiety from the first to the second measurement (p-value 0.034) and the first to the third measurement (p-value 0.000). Conclusion : Good Nutritional Style during preconception can improve nutritional status and minimize mental health risk. Nutrition intervention programs are needed to improve knowledge and implementation of healthy food nutrition. In addition, regular monitoring of nutritional status and mental health is also needed to optimize pregnancy readiness.